Brain literacy for educators and psychologists - Berninger, Virginia Wise (Practical resources for the mental health professional., 2002)
Although educators are expected to bring about functional changes in the brain--the organ of human learning--they are given no formal training in the structure, function or development of the brain in formal or atypically developing children as part of their education. This book is organized around three conceptual themes: First, the interplay between nature (genetics) and nurture (experience and environment) is emphasized. Second, the functional systems of the brain are explained in terms of how they lead to reading, writing and mathematics and the design of instruction. Thirdly, research is presented, not as a finished product, but as a step forward within the field of educational neuropsychology. The book differs from neuropsychology and neuroscience books in that it is aimed at practitioners, focuses on high incidence neuropsychological conditions seen in the classroom, and is the only book that integrates both brain research with the practice of effective literacy, and mathematics instruction of the general and special education school-aged populations.